The Association Between Insomnia and Erectile Dysfunction Among Udayana University Hospital Employees in 2025 - Putu Anindita Wira Cahyani; I Made Oka Negara; I Gusti Ngurah Pramesemara; I Gusti Ayu Widianti (Universitas Airlangga, 2026)
Background : Erectile dysfunction is the inability to achieve or maintain an erection sufficient for sexual activity. Insomnia is a sleep disorder that commonly occurs in individuals of productive age and may impact physiological functions of the body, including erectile function. Objective : This study aimed to determine the association between insomnia and erectile dysfunction among male employees of Udayana University Hospital. Methods : This analytical study was conducted with a cross-sectional design. The research respondents were obtained through purposive sampling and comprised 42 male employees aged 28–40 years. Data were collected using the Insomnia Severity Index (ISI) questionnaire to assess insomnia, and the International Index of Erectile Function-5 (IIEF-5) to assess erectile function. The collected data were then processed and analysed using SPSS 27 software. Results : Results indicated that 35.8% of respondents experienced insomnia, whereas 45.3% of respondents experienced erectile dysfunction. The chi-square test showed that males with insomnia had a four-fold higher risk of experiencing erectile dysfunction compared to those without insomnia (p=0.038). Conclusion : There is a significant association between insomnia and erectile dysfunction among male employees of Udayana University Hospital. Keywords : Insomnia, erectile dysfunction, IIEF-5 questionnaire, ISI questionnaire